Prediction of solar irradiation and performance evaluation of grid connected solar 80KWp PV plant in Bangladesh - Md. Bengir Ahmed Shuvho; Mohammad Asaduzzaman Chowdhury; Shameem Ahmed; Mohammod Abul Kashem (Energy Reports, 2019)
Energy security is the triggering factor for a developing country. Thus, for ensuring energy security renewable energy such as PV plant could be a best alternative. This study deals with the performance analysis of 80 KWp grid-connected solar power plant in Dhaka. This study presents a solar irradiation predict model based on fuzzy logic and artificial neural networks which aims to achieve a good accuracy at different weather conditions. The accuracy of predicted solar irradiation will affect the power output forecast of grid-connected photovoltaic systems which is important for power system operation and planning. Used data are taken from NASA. The performance of ANN is better than fuzzy logic model by comparing RMSE, R and percentage of accuracy. These fuzzy logic and ANN models can be used to forecast solar irradiation of Dhaka city in different environment condition and to provide enough information about the feasibility of solar power projects.
Keywords: 330; Photovoltaic; Fuzzy logic; ANN; Performance ratio; Sun simulator test